Comparison of the basic principles of green and sustainable chemistry concepts and their implementation in the QSAR methodology - Stetsenko, Natalia (My University, 2025)
The growth of global production and use of chemical products increases the risks associated with the adverse effects of hazardous chemicals on human health and the environment. In international practice, there is a shift in emphasis in regulating the circulation of chemical products. The use of administrative methods that require state-level control of the circulation of chemical substances, their mixtures and products derived from them is supplemented by methods to prevent the release of hazardous chemical products onto the market. The scientific direction of "green chemistry" aims to prevent the negative impact of chemicals on the environment and human health at the initial stages of chemical processes by reducing or completely eliminating the use of hazardous chemicals or improving the synthesis processes that produce these chemical substances. “Sustainable chemistry” is a scientific concept that aims to increase the efficiency of the use of natural resources to meet human needs for chemical products and services. Sustainable chemistry includes the development, production and use of effective, efficient, more environmentally friendly chemical products and processes. The principles of sustainable chemistry take into account the use of the best available technologies, increasing the life cycle of chemicals used in technological processes, and increasing resource and energy efficiency in order to achieve sustainable development. The application of the basic approaches and principles of both concepts in the formation and development of chemistry, chemical technologies and other industries is the driving force of sustainable industrial development. Зростання світового виробництва та використання хімічної продукції збільшує ризики, пов'язані з негативним впливом небезпечних хімічних речовин на здоров'я людини та довкілля. У міжнародній практиці спостерігається зміщення акцентів у регулюванні обігу хімічної продукції. Використання адміністративних методів, що вимагають контролю на державному рівні за обігом хімічних речовин, їх сумішей та продуктів, отриманих з них, доповнюється методами запобігання потраплянню на ринок небезпечної хімічної продукції. Науковий напрямок «зеленої хімії» спрямований на запобігання негативному впливу хімічних речовин на довкілля та здоров'я людини на початкових етапах хімічних процесів шляхом скорочення або повного виключення використання небезпечних хімічних речовин або вдосконалення процесів синтезу, на яких виробляють ці хімічні речовини. «Сталий розвиток хімії» – це наукова концепція, яка має на меті підвищення ефективності використання природних ресурсів для задоволення потреб людини в хімічних продуктах та послугах. Сталий розвиток хімії включає розробку, виробництво та використання ефективних, результативних, більш екологічно чистих хімічних продуктів та процесів. Принципи сталого розвитку хімії враховують використання найкращих доступних технологій, збільшення життєвого циклу хімічних речовин, що використовуються в технологічних процесах, та підвищення ресурсо- та енергоефективності з метою досягнення сталого розвитку. Застосування основних підходів та принципів обох концепцій у становленні та розвитку хімії, хімічних технологій та інших галузей промисловості є рушійною силою сталого промислового розвитку.
Keywords: green chemistry; chemicals; safe handling; зелена хімія; стала хімія; хімічні речовини; кафедра технології оздоровчих продуктів